Validity and reliability of resilience measurement model for student-athletes in Yogyakarta, Indonesia - Faidillah Kurniawan; Endang Rini Sukamti; Isti Yuni Purwanti; Novi Resmi Ningrum; Rajesh Kumar (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
The purpose of this study is to develop a valid and reliable resilience questionnaire model for student-athletes at the university level in Indonesia. It is an analytical survey with a correlational approach. The research analysis was done through Confirmatory Factor Analysis (CFA) with the help of LISREL 8.71. The questionnaire was developed through several stages: the first stage was the study of previous research, the second stage was the focus group discussion (FGD) involving lecturers from sports coaching and sports psychology, as well as coaches from several types of sports, the third stage was data collection, the fourth stage was the report of research results. The sample participating in this study was 245 athletes (147 male and 98 female), with several characteristics (mean±SD): maximum age was 21.7±8.9, minimum age was 18.4±3.3, average age was 20.5±2.8 years, training experience was 8.3±2.1 years, experience as an athlete was 4.8±7.7 years, and experience participating in competition was 2 – 4 times a year. The results of this study produced the questionnaire that features three aspects: 1) self-regulation, 2) personal competence, and 3) acceptance of one’s self and life. The loading factor value of each item in aspect >0.5 and T-value >1.96, and the fit model criteria showed Chi Square 1811.53, RMSEA 0.06, NFI 0.92, NNFI 0.93, CFI 0.91, PGFI 0.93, AGFI 0.92 which was fit. It can be concluded that the resilience questionnaire developed for student-athletes in Indonesia proved to be valid and reliable. Thus, this questionnaire can be an effective measuring tool as well as a guide for intervention programs aimed at increasing resilience and supporting optimal student- athletes achievement in Indonesia.